Diamond and DLC Layers for a Wide Range of Aplications - Marian Vojs; M. Vesely (Communications - Scientific letters of the University of Zilina, 2006)
Diamond and diamond-like carbon (DLC) layers are nowadays of increasing importance for electrical and mechanical applications. In our laboratory we grow diamond on different substrates (Si, WC-Co) using Hot Filament Chemical Vapor Deposition (HF CVD)method improved by double biasing and DLC layers using pulsed arc system again on different substrates (Si, Ni, glass, Ti-6Al-4V, steel, WCCo). Growth parameters facilitate to control crystallinity of diamond layers from microcrystalline to nanocrystalline type. Mechanical, electrical and optical parameters are possible to change using doping with hydrogen, nitrogen, or oxygen. The goal of this article is to summarize recent results achieved in our laboratory related to applications of diamond and DLC layers for their use in sensors of hard metal in water and medical implantable joints.